Accessibility requirements in public requests for tenders concerning public online services in Finland 2017–2023 - Janne Lahti; Markku Turunen (Universal Access in the Information Society, 2026)
Abstract The research focuses on the accessibility requirements in public requests for tenders concerning public online services in Finland from 2017 to 2023. According to Finnish legislation, published public online services must meet accessibility requirements. The study aims to understand the shortcomings of the current state of accessibility in public web services by analyzing the public procurement process. The procurement process sets the foundation by identifying requirements and specifications for development phase. The research examines the inclusion of accessibility requirements in public procurement documentation and how these requirements have evolved over time. The research also investigates the impact of legislation, standards, and guidelines on the procurement process and the accessibility of the resulting public online services in Finland. The study analyzed 66 different sets of tender documents from the period in question. The documents were retrieved from the commercial Mercell database, which compiles historical procurement data from Finland’s official HILMA public procurement system. The documents were selected using the search terms “online service” OR “website”. Based on these search terms, 170 procurement datasets from the selected period were identified fitting the scope, while 104 were excluded. The study points out findings on sanctions for Non-Compliance with accessibility standards, and other potential problems, such as inaccessible prototypes included in the bidding materials and responsibility issues when several different parties are involved in the project and user interface / user experience design. During the reviewed period (2017 to 2023), only half of the public calls for tenders included mandatory, legislation-based accessibility requirements, with varying quality. However, according to the study, the proportion of tenders containing accessibility requirements based on legislation has increased almost every year during the research period, reaching 80% in 2023.